2020
DOI: 10.1101/2020.04.10.20060855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety of Focused Ultrasound Neuromodulation in Humans with Temporal Lobe Epilepsy

Abstract: Objective: Low-Intensity Focused Ultrasound Pulsations (LIFUP) is a promising new potential neuromodulation tool. However, the safety of LIFUP neuromodulation has not yet been adequately assessed. Patients with refractory temporal lobe epilepsy electing to undergo an anterior temporal lobe resection present a unique opportunity to evaluate the safety and efficacy of LIFUP neuromodulation. Because the brain tissue in these patients will be removed, histological changes in tissue after LIFUP can be examined. Evi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In a separate investigation, exposures up to 8 times the intensity limit (up to ISPTA.3 of 5760 mW/cm 2 ) failed to produce a measurable in-situ temperature rise via MR thermometry [41].…”
Section: B Estimation Of In-vivo Exposurementioning
confidence: 89%
“…In a separate investigation, exposures up to 8 times the intensity limit (up to ISPTA.3 of 5760 mW/cm 2 ) failed to produce a measurable in-situ temperature rise via MR thermometry [41].…”
Section: B Estimation Of In-vivo Exposurementioning
confidence: 89%
“…RF‐TC is a less resource‐intensive alternative to LiTT. Focused ultrasound also has a potential use for neuromodulation in epilepsies 29 . There is compelling evidence of efficacy for these emerging minimally invasive approaches, 30,31 but recent meta‐analyses suggest waning seizure freedom over time across all types of epilepsy surgery, most noticeable in minimally invasive approaches 32,33 .…”
Section: Critical Definitions and Conceptsmentioning
confidence: 99%
“…Abe et al in Japan reported the first case of transcranial magnetic resonance-guided FUS (MRgFUS) for mesial temporal lobe epilepsy [83]. Further study in UCLA group on eight temporal lobe epilepsy patients before and after treatment with FUS using intensities up to 5760 mW/cm showed that there was no detectable damage to the tissue in the histological analysis of the resected specimens, and the neuropsychological testing results showed no significant changes after the treatment [84].…”
Section: Excitation In Mechanosensitive Membrane Induced By Radiation...mentioning
confidence: 99%